Effect of sintering temperature on mechanical behaviour and bioactivity of calcia-stabilized zirconia derived cockle shells bioceramic - Wahab, Nur Ain Adila Abd (2023)
The original experimental research carried out for this study by previous researcher was to investigate the synthesized of calcium oxide derived from cockle shells to be used as stabilizer for zirconia bioceramic at different temperatures. However, this research was continued by improved the production of calcium oxide derived from cockle shells using an improved protocol and determine its purity. Further, the improved data analysis of Ca-SZ bioceramic at different sintering temperatures were compared to the commercialized CEREC Sirona dental block. Hence, the aim of this study is to investigate the effect of sintering temperature on structural, morphological, mechanical, and biological properties of calcia-stabilized zirconia derived cockle shells bioceramic. To achieve this objective, three sintering temperatures at 1200 oC, 1300 oC and 1400 oC were selected in order to understand the structural, morphological and mechanical properties of Ca-SZ bioceramic after incorporation of 8 wt% of nano-CaO powders derived from cockle shells. Moreover, to give better comparative results, CEREC Sirona was sintered at temperature 1510 oC followed the protocol provided by Sirona, The Dental Company. In this experimental work, the diluted cockle shells powder was mixed with calcium chloride (CaCl2) and potassium carbonate (KCO3), using mechanochemical synthesis process. Then, nano-CaCO3 powder underwent calcination process at a temperature range of 300 oC – 550 oC to obtain nano-CaO powders. Nano-CaO powder derived from cockle shells were characterized using X-Ray Diffraction (XRD) analysis, Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscope (TEM) to ensure high purity of nano-CaO powder was obtained in fabricating Calcia-Stabilized Zirconia (Ca-SZ). FESEM and TEM analyses show that nano-CaCO3 produced hexagonal shape crystals while nano-CaO display spherical shape with crystal-like structure. Next, Ca-SZ bioceramic derived cockle shell powder obtained at different sintering temperature were then compacted and characterized using FESEM and XRD. Ca-SZ sintered at 1400 oC showed the highest mechanical properties and better in in-vitro test using SBF solution compared to other sintered specimens due to the pore size reduced within temperature rise. However, Ca-SZ sintered at 1400 oC produced lower mechanical strengths when compared to commercialized CEREC Sirona. Therefore, these findings revealed that by adjusting the previous protocol, improved, pure nano-CaO may be synthesized using natural Ca source from cockle shells. Additionally, the fabricated Ca- SZ has a potential in biological properties and also showed a significantly lower mechanical properties compared with CEREC Sirona when sintered at 1400 oC which may be easier for machining and has a potential to be commercialized soon which helps in study for dental treatment.